Dissecting implicit food-related behaviors in Binge Eating Disorder and obesity: insights from a mobile approach-avoidance framework - Collantoni, Enrico; Meregalli, Valentina; Granziol, Umberto; Di Vincenzo, Angelo; Rossato, Marco; Giovannini, Serena; Capobianco, Elisa; Zech, Hilmar; Vettor, Roberto; Favaro, Angela (Frontiers in Psychology, 2024)
Bulimic episodes experienced by patients with Binge Eating Disorder (BED) might be sustained by an enhanced behavioral propensity to approach food stimuli. To test this hypothesis, automatic approach avoidance tendencies toward high-calorie foods (HCF), low-calorie foods (LCF) and neutral objects were assessed in a group of 23 patients with BED, and their performance was compared to the one of 17 patients with obesity without BED and a group of 32 normal weight participants. All participants performed a mobile approach-avoidance task in which they were required to approach and avoid different stimuli by respectively pulling their phone towards themselves or pushing it away. Reaction times were analyzed. Results showed a significant three-way interaction between group, type of movement and stimulus. Post-hoc analyses revealed that all the groups displayed an approach bias toward HCF. Patients with BED and healthy controls also displayed an approach bias toward LCF, a bias that was absent in obese individuals without BED. Moreover, patients with BED were faster in approaching food stimuli, both HCF and LCF, compared to healthy controls. These behavioral tendencies are quite consistent with the real-life attitudes of both BED patients and patients with obesity and might contribute to the maintenance of unhealthy eating habits such as binging in patients with BED and high-calorie diets in patients with obesity.